2023
DOI: 10.4103/jehp.jehp_730_22
|View full text |Cite
|
Sign up to set email alerts
|

Stigmatizing attitude towards mental illness, disabilities, emotional and behavioural disorders, among healthcare students in a Tropical University College of Health Sciences

Abstract: BACKGROUND: Stigma toward mental illness (MI), physical disability (DA), and emotional/behavioral disorders (EBD) has been identified as a form of violence and a cause of nontake-up of help by people in need. Stigmatization can aggravate an individual's feeling of rejection and incompetence and can be detrimental to treatment-seeking and adherence behaviors. This study evaluated the attitude of healthcare students toward MI, DA, and EBDs. MATERIALS AND METHODS: This stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 41 publications
0
1
0
Order By: Relevance
“…While there is an issue with stigma around mental illness among healthcare practitioners, it is less clear from the literature how students in healthcare education programmes see and perceive mental diseases (Amaechi et al, 2023 ). In this study, we found that the majority of student participants were aware of the social stigma associated with mental illness.…”
Section: Discussionmentioning
confidence: 99%
“…While there is an issue with stigma around mental illness among healthcare practitioners, it is less clear from the literature how students in healthcare education programmes see and perceive mental diseases (Amaechi et al, 2023 ). In this study, we found that the majority of student participants were aware of the social stigma associated with mental illness.…”
Section: Discussionmentioning
confidence: 99%
“…A ECT ainda é estigmatizada e associada a práticas punitivas, apesar de atualmente ser um procedimento seguro e eficaz. Até hoje, pessoas comuns e profissionais que não estão atualizados ainda acreditam nessa ideia (Sadeghian et al, 2019. Amaechi et al, 2023da Silva, Baldaçara et al, 2020;Sadeghian et al, 2019).…”
Section: Resistências Da Equipe De Saúdeunclassified
“…Também foram notadas resistências quanto à estrutura física para realização da ECT que vão de dificuldades para locação de salas no centro cirúrgico até profissionais diversos que não se sentiam confortáveis durante o procedimento. (Amaechi et al, 2023;Sadeghian et al, 2019) Mesmo com alguns entraves, a ECT passou a ser vista como mais um procedimento terapêutico disponível para tratar doenças mentais.…”
Section: Resistências Da Equipe De Saúdeunclassified